Report on the 30th Young Pedagogues Summer School “Education Research Traps”, Katowice – Wisła, 12 - 16 September 2016 - Michalak-Dawidziuk, Joanna (Studia Edukacyjne, 2017)
Report on the 30th Young Pedagogues Summer School “Education Research Traps”, Katowice – Wisła, 12 - 16 September 2016